Quorum sensing mediates yeast cell morphology to improve settleability: Implication for wastewater treatment. Issue 5 (October 2021) - Sun, Jianmin; Sun, Huiping; Lv, Wenzhou; Zhang, Quandi; Wan, Pengfei; Jiang, Li; Zhong, Yingying
Abstract: The transformation of yeast cells from yeast to mycelium affects the settleability of yeast and the stability of the wastewater treatment system. In the present study, the dominant yeast strain of the wastewater treatment system, Candida tropicalis, and the mycelium inducer phenylalanine were used to explore the co-effect of cell density and the inducer on yeast cell morphology, flocculation, settleability and metabolism. The results revealed that a higher cell density had an excellent antagonism to filamentous induction condition to inhibit cell filamentation and thus achieve better cell flocculation and settleability. The mycelium ratio at a higher cell density (1 × 10 8 cfu/mL) was much lower than that at a lower one (1 × 10 6 cfu/mL), the mycelia length of the former is only 1/6 of that of the latter. With the cell density increased, the phenylalanine utilization decreased; the tyrosine and tryptophan-like proteins increased in extracellular substances; and the ethanol and small molecule fatty acids (acetic acid, propionic acid, butyric acid and valeric acid) decreased in metabolites, indicating that cell density remarkably affected yeast cell metabolism. The quorum-sensing molecule, phenethyl alcohol, was detected in metabolites and the concentration increased with the cell density, which proved that the essence of antagonism was quorum sensing between cells. This study provides a reference for regulating yeast cell transformation in wastewater treatment to increase the system stability. Graphical Abstract: ga1 Highlights: Phenylalanine was used to simulate the mycelium inducer in wastewater treatment. Cell density revealed an excellent antagonism to cell filamentation under induction. Cell density affected phenylalanine utilization and metabolites of yeast cells. A quorum sensing molecule phenethyl alcohol was detected under a higher cell density. The essence of antagonism to the inducer was quorum sensing between yeast cells.